A New Selective Pharmacological Enhancer of the Orai1 Ca(2+) Channel Reveals Roles for Orai1 in Smooth and Skeletal Muscle Functions - Azimi, Iman (ACS Pharmacol Transl Sci, 2020)
[Image: see text] Store-operated calcium (Ca(2+)) entry is an important homeostatic mechanism in cells, whereby the release of Ca(2+) from intracellular endoplasmic reticulum stores triggers the activation of a Ca(2+) influx pathway. Mediated by Orai1, this Ca(2+) influx has specific and essential roles in biological processes as diverse as lactation to immunity. Although pharmacological inhibitors of this Ca(2+) influx mechanism have helped to define the role of store-operated Ca(2+) entry in many cellular events, the lack of isoform specific modulators and activators of Orai1 has limited our full understanding of these processes. Here we report the identification and synthesis of an Orai1 activity enhancer that concurrently potentiated Orai1 Ca(2+)-dependent inactivation (CDI). This unique enhancer of Orai1 had only a modest effect on Orai3 with weak inhibitory effects at high concentrations in intact MCF-7 breast cancer cells. The Orai1 enhancer heightened vascular smooth muscle cell migration induced by platelet-derived growth factor and the unique store-operated Ca(2+) entry pathway present in skeletal muscle cells. These studies show that IA65 is an exemplar for the translation and development of Orai isoform selective agents. The ability of IA65 to activate CDI demonstrates that agents can be developed that can enhance Orai1-mediated Ca(2+) influx but avoid the cytotoxicity associated with sustained Orai1 activation. IA65 and/or future analogues with similar Orai1- and CDI-activating properties could function to fine-tune physiological processes important in specific disease states, such as cellular migration and immune cell function.